Dilution of the Antarctic ozone hole into southern midlatitudes, 1998-2000 - Ajtic, J.; Connor, B. J.; Lawrence, B. N.; Bodeker, G. E.; Hoppel, K. W.; Rosenfield, J. E.; Heuff, D. N. (Journal of Geophysical Research, 2004)
The reduction in southern midlatitude ozone is quantified by evaluating the trajectories of ozone-depleted air masses, assuming that photochemical recovery of ozone in advected air parcels can be ignored. This procedure is carried out for the 3 months from 15 October to 15 January for each of the years 1998, 1999, and 2000. Two distinct source regions, the vortex core and the vortex edge, are considered, and for each day, diabatic reverse domain filling calculations are performed for an ensemble of parcels between 30°S and 60°S and 400–700 K in altitude. In 1998, 1999, and 2000 the mean calculated ozone reduction is 16, 18, and 19 DU, respectively. Air parcels from the vortex edge region are significant contributors to the reduction, especially during spring. Results for four longitudinal and three latitudinal midlatitude subregions are also presented. A comparison with the Total Ozone Mapping Spectrometer measurements of total column ozone shows that without the dilution, ozone over Southern Hemisphere midlatitudes would be 5–6% higher during spring and summer. This result is probably an overestimate due to the neglect of photochemical recovery.